Temporal trends of cancer incidence rates for the most frequent cancer sites in Cyprus (2004-2017) - Spartiati, Anastasia; Demetriou, Anna; Scoutellas, V; Christophi, Costas A.; Makris, Konstantinos C. (My University, 2024)
Cancer is one of the leading causes of morbidity and mortality, worldwide. Little information is available for the temporal trends of cancer in the Mediterranean region, including Cyprus.
Keywords: annual percentage change; breast; cancer; joinpoint; thyroid